Efektivitas Penerapan CHSE ( Clean, Health, Safety & Environment ) Pada Hotel Katagori Bintang 3 (Tiga) di Kota Depok - Sofiani; Vivian Octariana (Samarinda State Polytechnic, 2021)
The CHSE (Clean, Health, Safety & Environment) Certification Program or Hygiene, Health, Safety, and Environmental Sustainability is granting certificates to tourism businesses, other related businesses/facilities, community environments, and tourism destinations. CHSE certification serves as a guarantee to tourists and the public that the products and services provided have complied with the hygiene, health, safety, and environmental sustainability protocols. The average result of the total questionnaire variable CHSE (X) in 3-star category hotels in Depok is 72% which is classified in the good category. From all statement indicators, I can see that we find the lowest indicator in guests washing hands with soap/hand sanitised before and after entering the restaurant, this is because of the unavailability of a place to wash hands in the restaurant area. From all statement indicators, I can see that they find the highest indicator in the transportation party. Here, the driver/guest carries out the guidelines for parking the vehicle following existing instructions and rules with a result of 78%. From the results of simple linear regression analysis, I found that the CHSE variable X affected the decision to stay.